Development and performance tests of a sedimentation trap for silt and clay particles - Ewat, Pedo (Universiti Malaysia Sarawak (UNIMAS), 2006)
This research project focuses on the design, development and performance tests of a sedimentation trap model regarding to its usage in civil engineering construction site to remove or reduce the suspended solids (SS), especially for light soil particles such as silt and clay contained in the surface runoffs.